Association of NIPA1 repeat expansions with amyotrophic lateral sclerosis in a large international cohort - Tazelaar, Gijs H. P.; Dekker, Annelot M.; van Vugt, Joke J. F. A.; van der Spek, Rick A.; Westeneng, Henk-Jan; Kool, Lindy J. B. G.; Kenna, Kevin P.; van Rheenen, Wouter; Pulit, Sara L.; McLaughlin, Russell L.; Sproviero, William; Iacoangeli, Alfredo; et al. (Neurobiology of aging, 2019)
NIPA1 (nonimprinted in Prader-Willi/Angelman syndrome 1) mutations are known to cause hereditary spastic paraplegia type 6, a neurodegenerative disease that phenotypically overlaps to some extent with amyotrophic lateral sclerosis (ALS). Previously, a genomewide screen for copy number variants found an association with rare deletions in NIPA1 and ALS, and subsequent genetic analyses revealed that long (or expanded) polyalanine repeats in NIPA1 convey increased ALS susceptibility. We set out to perform a large-scale replication study to further investigate the role of NIPA1 polyalanine expansions with ALS, in which we characterized NIPA1 repeat size in an independent international cohort of 3955 patients with ALS and 2276 unaffected controls and combined our results with previous reports. Meta-analysis on a total of 6245 patients with ALS and 5051 controls showed an overall increased risk of ALS in those with expanded (>8) GCG repeat length (odds ratio = 1.50, p = 3.8×10−5). Together with previous reports, these findings provide evidence for an association of an expanded polyalanine repeat in NIPA1 and ALS.
Online verfügbar: 22 September 2018
Gesehen am 15.07.2021